PENGARUH DANA ZAKAT DALAM PROGRAM BEASISWA ABA (AYAH BUNDA ASUH) TERHADAP KESEJAHTERAAN SPIRITUAL MUSTAHIK LAZ YASA MALANG - Marlina Ekawaty; Anugrah Pratama, Muhammad Akbar (Islamic Economics and finance in Focus, 2023)
This research aims to investigate the implementation of the ABA LAZ YASA Malang scholarship program and the impact of the scholarship on the spiritual well-being of the recipients. The research method used is descriptive quantitative, and the data analysis technique employs the CIBEST model. The study involves 100 respondents selected through purposive sampling. The results of the analysis, using SPSS 26 software for the normality test, indicate that the data is not normally distributed. Therefore, the Wilcoxon test was conducted, which revealed that the positive ranks or the positive difference between the spiritual activities before and during the mentoring program showed an increase among 79 beneficiaries. This suggests an improvement in their spiritual engagement.